Use of weathered diesel oil as a low-cost raw material to biosurfactant production - Mariano, Adriano Pinto [UNESP]; Bonotto, Daniel Marcos; De Franceschi De Angelis, Dejanira; Pirôllo, Maria Paula Santos [UNESP]; Contiero, Jonas (My University, 2006)
This work aimed to investigate the capability of biosurfactant production by bacteria cultures of Staphylococcus hominis, Kocuria palustris and Pseudomonas aeruginosa LBI, isolated from hydrocarbon contaminated areas, using weathered diesel oil from a long-standing spillage as raw material. It was evaluated the influence of the culture media (Robert or Bushnell-Haas) and of the carbon source (spilled diesel oil or commercial diesel oil) in the biosurfactant production. Erlenmeyer flasks (250 mL) containing the cell broth were agitated (240 rpm) for 144 h. The monitoring of the biosurfactant production was carried out measuring the surface tension of the cell free culture, according to the De Nöuy ring method using the Krüss K6 tensiometer. Considering the possibility of intracellular storage of biosurfactant in the cell wall of the cultures S. hominis and K. palustris, tests were also done applying ultrasound as a way to rupture the cells. For the studied conditions, the cultures did not indicate biosurfactants production. Results obtained with a hydrocarbon biodegradability test employing the redox indicator 2,6 - dichlorophenol indophenol showed that only the commercial diesel is biodegraded by the cultures.
Keywords: Biosurfactant; Raw material; Weathered diesel oil